Rating of perceived exertion and heart rate as indicators of exercise intensity in different environmental temperatures - Potteiger, J. A.; Weber, S. F. (Medicine & Science in Sports & Exercise, 1994)
Nine cyclists performed the same task under three temperature conditions (30, 22, and 14 degrees Celsius). HR and RPE were determined at various stages of the tasks. It was concluded that HR was a more valid marker of exercise intensity than RPE. In this study it is possible that RPE included more stress variables than those of a pure physiological nature. Implication: In some circumstances, particularly where conditions of exercise change rapidly, it might be better to monitor exercise application levels with RPE and physiological variables. However, when individuals are very familiar with a training environment and activity, it still appears that RPE is a more accurate and sensitive measure of exercise stress.